1983
DOI: 10.1111/j.1600-0447.1983.tb00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Father/son relationship during the preschool years: An integrative review with special reference to recent Swedish findings

Abstract: This review is an attempt to integrate Anglo-American and Swedish studies on father/son relationships. The puerperal period, infancy and early childhood are surveyed. Swedish studies do not support specific stereotyped bonding in the puerperal period. The review confirms the bidirectional nature of the father/son relationship. Thus, counteridentification, i.e. the father's identification with his son, and identification during the oedipal phase, i.e. the son's identification with his father, seem to be essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The lack of paternity-leave policies means that many women must carry double the workload of most men, fulfilling their job responsibilities as well as the majority of household responsibilities; that men do not get the same opportunities as women to develop relationships with their children; and that children are unlikely to receive as much parental care as they would otherwise benefit from. Providing paid paternity leave is essential to increase fathers' roles in the household and to enhance gender equity at home and at work, both of which have an impact on children's well-being and healthy development (Johnson et al, 1979;Taubenheim, 1981;Lamb, 1982;Anisfeld and Lipper, 1983;Nettelbladt, 1983;Mertin, 1986;Avery, 1992;Crouch and Manderson, 1995). There is substantial evidence that increases in maternal income disproportionately benefit children (Thomas, 1993;Quisumbing and Maluccio, 1999).…”
Section: Parental Leavementioning
confidence: 99%
“…The lack of paternity-leave policies means that many women must carry double the workload of most men, fulfilling their job responsibilities as well as the majority of household responsibilities; that men do not get the same opportunities as women to develop relationships with their children; and that children are unlikely to receive as much parental care as they would otherwise benefit from. Providing paid paternity leave is essential to increase fathers' roles in the household and to enhance gender equity at home and at work, both of which have an impact on children's well-being and healthy development (Johnson et al, 1979;Taubenheim, 1981;Lamb, 1982;Anisfeld and Lipper, 1983;Nettelbladt, 1983;Mertin, 1986;Avery, 1992;Crouch and Manderson, 1995). There is substantial evidence that increases in maternal income disproportionately benefit children (Thomas, 1993;Quisumbing and Maluccio, 1999).…”
Section: Parental Leavementioning
confidence: 99%
“…For example, there is no shortage of literature that underscores the importance of fathers in the family system. Almost all of it has been aimed at linking qualities of fathers and of their ties with their children to the adjustment of these children (e.g., Nettelbladt, 1983; Phares & Compas, 1992). For example, the husband's involvement in the care of young children is associated with more marital satisfaction and less depression in his wife.…”
Section: A Model Of Maternal Adjustmentmentioning
confidence: 99%
“…The impact of the bond between fathers and infants has been a growing area of research in recent years. 47,48 In the absence of paternity and family leave policies, men do not have the same opportunities as women to develop relationships with their children and aging family members, many women carry double the workload of most men through a combination of paid and unpaid work, children are unlikely to receive as much parental care, marriages are placed under greater stress, 49 and new mothers are more likely to suffer from maternal depression. 50 Paternity leave policies offer a significant advantage over parental leave in terms of promoting gender equality: it has been demonstrated that when leave is available that can only be used by the father, fathers are more likely to take leave and stay at home to care for a new child than when the leave available can be used by either or both parents.…”
mentioning
confidence: 99%